A Cross Country Prescriptive Analysis of the Efficiency of Educational Systems - Marcenaro-Gutiérrez, Óscar David (My University, 2016)
How does a country achieve the most efficient education system possible? We examine the efficiency of educational systems across the world using internationally comparable performance of secondary school pupils. We use OECD aggregate panel data on 39 countries across 15 years to model the most efficient combination of teacher salaries and class size to secure the maximum level of students’ achievement. Prescriptive policy evaluations are provided on how countries could make a significant improvement to their educational outcome by adjusting their educational resource inputs. We also ask if there is a trade-off between the efficiency and equity of educational provision.
CONGRESO INTERNACIONAL
Keywords: Efficiency; Equity; Stochastic frontier analysis